The Role of Human Capital Development and Innovation in Healthcare organizations of Markazi Province in Iran - Mohammad Reza Goodarzi; Anahita Goodarzi; Effat Goodarzi (Journal of Health Management & Informatics, 2016)
Introduction: Increase of environmental challenges inevitably changes our methods; challenges such as rapid change, diversity of workforce, globalization, evolution and transformation of business and family roles, lack of skills and emergence of service sector affect not only the organizational structure but also the nature and functional role of business. In response to these environmental challenges and in order to increase the efficiency and effectiveness and ultimately the productivity, the organizations have shifted toward two facilitators: human capital development and innovation. The aim of the current study is to survey the correlation between these two facilitators. Method: This research is a descriptive-analytical survey. The current research population includes all experts and managers of healthcare organizations of Markazi Province in Iran in January 2015. The statistical population consisted of 650 individuals; 180 individuals were chosen as the statistical sample using Cochran’s formula. In terms of data collection method, this is a descriptive-bivariate correlative type research. Library and internet resources developed based on the variables were used for collecting data related to theoretical concepts and extracting primary elements and indicators. Cronbach’s alpha test has been used for confirming the validity and reliability of the questionnaire (0.863) which indicates a high reliability. The number of collected questionnaire was 180 and they have been analyzed using Spearman correlation. Results:According to t-statistic in all hypotheses which is out of the range of -1.96-1.96, it could be said that human capital development, healthcare management, infrastructure of official institutions, infrastructure of unofficial institutions and knowledge (education) management development have a significance effect on innovation at significance level of 95%. As a result, all research hypotheses were confirmed. Conclusion: Innovation in inputs results in increased efficiency of employees especially in educational sections of the organization. According to the creative problem-solving process in ideal situation (truth finding-finding ideas and solutions), the organization can deal with the changes imposed on the system and reach the goal of more efficiency.